Promoting Academic and Nonacademic Behaviors in Students With EBD Using the Self-Determined Learning Model of Instruction: A Mathematics Example. (December 2020) - Pulos, Joshua M.; Peltier, Corey; Williams-Diehm, Kendra L.; Martin, James E.
Teaching self-determination to students with emotional and behavioral disorders (EBD) may empower them to become self-regulated problem solvers. This article, using the Self-Determined Learning Model of Instruction (SDLMI), outlines a framework for teachers to facilitate mathematics instruction and goal attainment relative to in-school and postschool outcomes. The SDLMI's three phases enable teachers to promote self-directed learning in their students with EBD. These increased opportunities of self-regulated learning can improve students' in-school and postschool success.